Homogeneous precipitation synthesis and thermoelectric properties of Ca2Co2O5 ceramics. (1st August 2013) - Chen, S B; Wang, H D; Wan, W; Huang, X
Abstract : Homogeneous precipitation method was applied to synthesise Ca2 Co2 O5 powders using calcium nitrate, cobalt nitrate and urea as raw materials. Uniform plate-like Ca2 Co2 O5 powders with an average grain size of 1 μm can be obtained by calcining the precursor for 8 h at 1073 K in the air. The Ca2 Co2 O5 ceramics were gained after sintering for 4 h at 1083 K using uniaxial pressure moulding and then sintering technique. The thermoelectric properties of ceramic samples were measured from 303 to 973 K, and the result shows that the electrical conductivity, Seebeck coefficient, thermal conductivity and figure of merit of the sample are 2236·85 S m −1, 175·95 μV K −1, 1·01 W m −1 K −1 and 0·69 at 973 K respectively.